DAMPAK PEMBATASAN JUMLAH KATA DAN HALAMAN PADA KEMAMPUAN PRESENTASI MAHASISWA - AENG MUHIDIN (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2018)
ABSTRAK Presentation is an integral part of learning in college. Microsoft Powerpoint and others like to give students the opportunity to make a fully prepared prepared text. Some suggestions for suggestions for improving text presentation slides. The literature review identifies the lack of research that addresses slide text transfer when applied text restrictions on student presentation slides. This article examines the impact of student perceptions on the preparation and presentation quality when applied text restrictions on slides and notes. These findings arise from a descriptive survey that discusses the students' perceptions of their class presentation when text restrictions are imposed both in terms of presentation visualizations and on notes for the final presentation of the course of Research Methods. Kata Kunci: Slide, Notetaking, Presentation, Powerpoint, Student